Inhibition of HIF2α Is Sufficient to Suppress pVHL-Defective Tumor Growth - Kondo, Keiichi (Public Library of Science, 2003)
Biallelic inactivation of the von Hippel–Lindau tumor suppressor gene (VHL) is linked to the development of hereditary (VHL-associated) and sporadic clear-cell renal carcinomas as well as other abnormalities. The VHL gene product, pVHL, is part of an E3 ubiquitin ligase complex that targets the α subunits of the heterodimeric transcription factor HIF (hypoxia-inducible factor) for degradation in the presence of oxygen. Here we report that a HIF2α variant lacking both of its two prolyl hydroxylation/pVHL-binding sites prevents tumor inhibition by pVHL in a DNA-binding dependent manner. Conversely, downregulation of HIF2α with short hairpin RNAs is sufficient to suppress tumor formation by pVHL-defective renal carcinoma cells. These results establish that tumor suppression by pVHL is linked to regulation of HIF target genes.